Exploring the use of workplaces to recruit "hard-to-reach" male drinkers to a survey on alcohol use and awareness of health messages - Sarah Dance; Charlotte Dack; Celia Lasheras; Cathy McMahon; Paul Scott; Sally Adams (BMC, 2021)
Abstract Background Lower socioeconomic status (SES) groups, particularly lower SES males, are at greater risk of alcohol-related harm than higher SES groups, despite drinking at the same level or less. However, they are rarely recruited for research through typical recruitment strategies. Consequently, limited evidence exists on patterns of alcohol use and effectiveness of public health messages for these groups. Using workplaces to recruit male drinkers from lower SES backgrounds may provide a feasible and accessible approach to research participation and enable improved understanding of alcohol use, drinking motives and acceptance of alcohol-related public health messages in this underrepresented and high-risk group. We investigated workplace-based strategies to recruit male drinkers from lower SES backgrounds. We also investigated their experiences and motivations for alcohol use, and acceptance of alcohol-related public health messages. Methods A feasibility element investigated the effectiveness of workplace-based strategies to recruit male drinkers from lower SES backgrounds in the south west of England. A pilot element investigated this population's experiences and motivations for alcohol use, and acceptance of alcohol-related public health messages, through a mixed-methods survey. Results Feasibility results indicated that workplace-based recruitment strategies, including recruiting participants in person at their workplace and providing a financial incentive, effectively led to the recruitment of 84 male drinkers (70% recruitment rate), predominately from lower SES backgrounds, to a survey. Pilot results indicated that more than half of participants were at increasing risk of alcohol-related harm, and approximately one fifth engaged in weekly heavy episodic drinking. Participation in campaigns aimed at reducing alcohol use, and knowledge of government alcohol consumption guidelines, were low. Participants reported negative beliefs about alcohol including health effects, dependency and excess use, and financial and occupational effects. Positive beliefs about alcohol included relaxation, socialising, and enjoyment. Conclusions Workplace-based recruitment, using in-person recruitment and a financial incentive, may be a feasible strategy to recruit male drinkers from lower SES backgrounds. Pilot results may direct larger scale research aiming to understand alcohol use in this population and inform targeted public health messages. Workplace-based recruitment may represent a promising avenue for future research aiming to tackle inequalities in participation in alcohol research.